2019
DOI: 10.3892/etm.2019.7609
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces apoptosis of HUVECs in a mitochondria‑dependent manner by suppressing hexokinase 2 expression

Abstract: Hyperglycemia in patients with diabetes induces vascular endothelial cell apoptosis and subsequent vasculopathy. The aim of the current study was to investigate the pathological mechanism of hyperglycemia-induced endothelial cell apoptosis and vasculopathy using human umbilical vein endothelial cells. As high glucose-induced apoptosis is caused by elevated mitochondrial permeability-mediated release of mitochondrial cytochrome c, the current study examined voltage-dependent anion channel (VDAC1), the controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
(34 reference statements)
3
14
0
Order By: Relevance
“…The antidiabetic drugs metformin and rosiglitazone restore the structure of MAM contacts in diabetic animals [ 168 ]. It should be noted that diabetes mellitus is associated with overexpression of VDAC1 in certain tissues (pancreatic β-cells, vascular endothelial cells) [ 169 , 170 , 171 ]. In parallel, an increased amount of Ca 2+ accumulates in mitochondria, which ultimately leads to the activation of apoptosis.…”
Section: Ca 2+ Handling Mpt Pore and Diabetes mentioning
confidence: 99%
See 1 more Smart Citation
“…The antidiabetic drugs metformin and rosiglitazone restore the structure of MAM contacts in diabetic animals [ 168 ]. It should be noted that diabetes mellitus is associated with overexpression of VDAC1 in certain tissues (pancreatic β-cells, vascular endothelial cells) [ 169 , 170 , 171 ]. In parallel, an increased amount of Ca 2+ accumulates in mitochondria, which ultimately leads to the activation of apoptosis.…”
Section: Ca 2+ Handling Mpt Pore and Diabetes mentioning
confidence: 99%
“…In parallel, an increased amount of Ca 2+ accumulates in mitochondria, which ultimately leads to the activation of apoptosis. Inhibition of VDAC1 overexpression leads to the suppression of apoptosis in endothelial cells and improves insulin secretion in islets [ 170 , 171 ].…”
Section: Ca 2+ Handling Mpt Pore and Diabetes mentioning
confidence: 99%
“…A previous study demonstrated that expression of lactate is increased under oxidative stress along with a reduction of LDHA expression, leading to the consumption of glucose [36], and these processes might be mediated by the MAPK signalling pathway [14]. A recent study also found that overexpression of HK2 might reduce the apoptosis of cells induced by high glucose with a reduction in Bax expression [45]. MDH2 is essential for the conversion of malate to oxaloacetate as part of the proper functioning of the Krebs cycle [7].…”
Section: Discussionmentioning
confidence: 97%
“…Growth factors, DNA damage, intracellular Ca 2+ and oxidative stress are the main triggers for the intrinsic pathway [ 69 , 70 ]. They induce upregulation of mitochondrial Bax and the downregulation of hexokinase 2 and Bcl-2 [ 71 ] and determine the cell death. ROS generation in hyperglycemia due to protein glycation, protein kinase C activation or mitochondrial oxidative phosphorylation is closely related to apoptosis and the inhibition of their production under PhyF exposure reduces caspase-3 active form and apoptosis and promotes cell recovery.…”
Section: Discussionmentioning
confidence: 99%